2011
DOI: 10.1158/1538-7445.am2011-4223
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4223: Possible usefulness of spirulina platensis for supression of some cases of hepatocellular carcinoma, multiple case study

Abstract: Backgrownd and study aims; One of the most frequent carcinoma through the world is hepato cellular carcinoma (HCC). It is rapidly fatal with a life expectancy of about 6 months from the time of diagnosis. The disease is more prevalent in parts of Africa and Asia with a strong etiological association with viral hepatitis, haemochromatosis, known carcinogen and toxins. There are many therapeutic options for HCC including; surgical operations, chemotherapy, radiofrequency, immune therapy and gene therapy. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study showed that spirulina did not have an antitumour effect against solid Ehrlich's carcinoma and increased mortality when combined with the standard chemotherapeutic drug 5-fluorouracil. These findings indicate that the anticancer effects of spirulina are not always positive and there's other herbal extract may by used with it to increase the effect [60]. This study could be useful to health professionals, teachers and researchers who wish to expand their knowledge about spirulina.…”
Section: Cytotoxic and Anticancer Activitiesmentioning
confidence: 84%
“…The study showed that spirulina did not have an antitumour effect against solid Ehrlich's carcinoma and increased mortality when combined with the standard chemotherapeutic drug 5-fluorouracil. These findings indicate that the anticancer effects of spirulina are not always positive and there's other herbal extract may by used with it to increase the effect [60]. This study could be useful to health professionals, teachers and researchers who wish to expand their knowledge about spirulina.…”
Section: Cytotoxic and Anticancer Activitiesmentioning
confidence: 84%